Morphological description of tooth surfaces after application of casein phosphopeptide-amorphous calcium phosphate paste : Gambaran morfologi permukaan gigi pasca-aplikasi pasta casein phosphopeptide-amorphus calcium phosphate - Said, Annisa Rahma; Amin, Asmawati; Talib, Bahruddin; Thalib, Alqarama Mahardhika (Makassar Dental Journal, 2025)
The use of hydrogen peroxide bleaching agents can disrupt tissue permeability, causing lesions due to the demineralisation pro-cess caused by the acidic nature of the bleaching agent. A remineralisation agent is required. Casein phosphopeptide-amorph-ous calcium phosphate (CPP-ACP) is a widely used material in preventive dentistry and has been proven to provide protection against acid. This article provides an overview of the surface morphology of teeth treated with CPP-ACP paste. The study was an experimental laboratory design with a pre-posttest and control group. Ten samples were evenly divided into two groups: control and treatment. The control samples were immersed in artificial saliva for 24 hours and then rinsed with distilled water. The treat-ment samples were treated with 35% hydrogen peroxide for 2 hours, then cleaned with distilled water and observed using SEM. Subsequently, CPP-ACP paste was applied every 8 hours for 14 consecutive days, followed by SEM observation. CPP-ACP paste was found to help inhibit demineralisation and enhance the remineralisation process of teeth. It was concluded that teeth treated with CPP-ACP paste appeared smooth with minimal shallow scratches and exhibited porosity around them with small pore sizes.